(untitled) (Polis (Santiago), 2018)
The article claims that the information technological revolution is overturning all domains of social reality, likewise the other two great technological revolutions –those of steam and of electricity- that marked contemporary history. We are currently witnessing the emergence of a new civil society that goes beyond the borders of nation-states and operates in real-time unit and globally. The text covers the main features of Social Network Analysis, designed as a promising analytical approach that allows us to grasp the emerging organizational logic.